The design of analog electronic instructional video at vocational schools in Manado - Christine Manoppo, (Technium Social Sciences Journal, 2023)
This research is a learning media development research with a research and development model. The long-term goal of this research is to design basic electronics instructional videos for Vocational School students in Manado. Video is a device used for learning activities in the process of presenting material in the form of images and sound. So that students will be able to receive visual and auditory Basic Electronics information factually. This subject matter discusses electronic components, including passive and active components. The research was held in 3 years; the first year was to carry out field observations by observing the learning process in SMK, the second year was to specifically design and test the products, and the third year was to produce products and applications, as well as product publications. All was done in Vocational School in Manado.